1988
DOI: 10.2307/1940452
|View full text |Cite
|
Sign up to set email alerts
|

The Analysis of Class Dispersion Patterns Using Matrix Comparisons

Abstract: A matrix comparison method is demonstrated for measuring the relative dispersion of different classes of individuals (e.g., species, age classes, life forms) in a sample of plants whose distributions has been mapped. The method employs combinatorial data analysis procedures and a Monte Carlo approach to significance testing; it is particularly suited to the study of subsets of interplant distances in relatively small data sets. As an example, within—site tree dispersion patterns in a Jamaican wet limestone for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…soil and micrometeorological properties). Many studies have shown soil properties to be heterogeneous over a distance of a few meters (Robertson et al 1988;Palmer & Dixon 1990) and this would be especially true for the makatea where soil collects in pockets on the pit and pinnacle karst (Harvey, Davis & Gale 1988).…”
Section: Discussionmentioning
confidence: 99%
“…soil and micrometeorological properties). Many studies have shown soil properties to be heterogeneous over a distance of a few meters (Robertson et al 1988;Palmer & Dixon 1990) and this would be especially true for the makatea where soil collects in pockets on the pit and pinnacle karst (Harvey, Davis & Gale 1988).…”
Section: Discussionmentioning
confidence: 99%
“…The spatial patterns of white vc types and white isolates on the grafted trees were determined using the double matrix test of HARVEY et al (1988). One matrix contained the distances between the cankers and the white hypovirulent strain-inoculated zone on the stem, and the second matrix indicated whether isolates belonged to the same culture type or vc type.…”
Section: Spatial Pattern Of White Vc Types On the Grafted American Chmentioning
confidence: 99%